A recombinant iron transport protein from Bordetella pertussis confers protection against Bordetella parapertussis. (26th September 2017) - Alvarez Hayes, Jimena; Oviedo, Juan Marcos; Valdez, Hugo; Laborde, Juan Martín; Maschi, Fabricio; Ayala, Miguel; Shah, Rohan; Fernandez Lahore, Marcelo; Rodriguez, Maria Eugenia
ABSTRACT: Whooping cough, which is caused by Bordetella pertussis and B. parapertussis, is a reemerging disease. New protective antigens are needed to improve the efficacy of current vaccines against both species. Using proteomic tools, it was here found that B. parapertussis expresses a homolog of AfuA, a previously reported new vaccine candidate against B. pertussis . It was found that this homolog, named AfuABpp, is expressed during B. parapertussis infection, exposed on the surface of the bacteria and recognized by specific antibodies induced by the recombinant AfuA cloned from B. pertussis (rAfuA). Importantly, the presence of the O‐antigen, a molecule that has been found to shield surface antigens on B. parapertussis, showed no influence on antibody recognition of AfuABpp on the bacterial surface. The present study further showed that antibodies induced by immunization with the recombinant protein were able to opsonize B. parapertussis and promote bacterial uptake by neutrophils. Finally, it was shown that this antigen confers protection against B. parapertussis infection in a mouse model. Altogether, these results indicate that AfuA is a good vaccine candidate for acellular vaccines protective against both causative agents of whooping cough.